Identification factors to adjust early combination regimens in adult primary immune thrombocytopenia: An 8-year data analysis - Iam-arunthai, Kunapa; Chamnanchanunt, Supat; Thungthong, Pravinwan; Nakhahes, Chajchawan; Suwanban, Tawatchai; Rojnuckarin, Ponlapat (Frontiers in Hematology, 2023)
Purpose: Recent studies suggested that adding other agents to corticosteroids as a first-line treatment for immune thrombocytopenia (ITP) could improve outcomes. However, combination regimens may increase side effects and costs. To determine clinical factors associated with responses to the first-line steroid at 1 month. Materials and methods: We retrospectively reviewed the medical records of patients with ITP aged > 18 years, who were treated at Rajavithi Hospital between 2012 and 2020. Clinical data, laboratory results, treatment regimens, and responses to therapy were analyzed. Results: Of the 226 patients, 76.6 % were female. The mean age was 46.5 ±18.1 years, and the median follow-up duration was 40 months. The proportion of chronic ITP was 97.3%. The complete response and response rates to first-line therapy was 65.5% and 88.9%, respectively. The age over 26 years, presentation clinically non-significant bleeding and a difference in platelet count of >50 x 109 /L between days 1 and 7 after initial treatment were associated with the response to first-line treatment (adjusted odds ratio [OR] 5.09, 95% confidence interval [CI] 1.50-17.28, p = 0.009); OR 5.87, 95%CI 1.19-28.91, p = 0.029, and OR 3.60, 95%CI 1.10-11.73, p = 0.034, respectively. Younger patients and a difference in platelet count between day 1 and 7 < 50 x 109 /L were more likely to require second-line treatments. There were significant increases in the median platelet counts after prescribing azathioprine (baseline vs. 3 months, p = 0.001), cyclophosphamide (baseline vs. 6 months, p = 0.021), or danazol (baseline vs. 12 months, p = 0.039). Conclusion: Adult, severity of bleeding at presentation, and rapid platelet increases within 1 week were related to excellent corticosteroid responses in ITP patients. These patients may not need combination regimens.